Seasonal increase in nest defense, but not egg rejection, in a cuckoo host - Bo Zhou; Wei Liang (Avian Research, 2024)
The interactions between avian brood parasites and their hosts provide an informative and easy-to-handle system for studying coevolution. Avian brood parasitism reduces the reproductive success of hosts, and thus, hosts have evolved anti-parasitic strategies, such as rejecting parasitic eggs and adopting aggressive nest defense strategies, to avoid the cost brought on by brood parasitism. To test whether host anti-parasitic strategies are adjusted with the risk of being parasitized when the breeding seasons of brood parasites and hosts are not synchronous, we conducted a field experiment assessing nest defense and egg recognition behaviors of the Isabelline Shrike (Lanius isabellinus), a host of the Common Cuckoo (Cuculus canorus). In the local area, the host Isabelline Shrike begins to breed in April, whereas the summer migratory Common Cuckoo migrates to the local area in May and begins to lay parasitic eggs. Results showed that nest defense behaviors of the Isabelline Shrike increases significantly after cuckoo arrival, showing higher aggressiveness to cuckoo dummies, with no significant difference in attack rates among cuckoo, sparrowhawk and dove dummies, but their egg rejection did not change significantly. These results imply that Isabelline Shrikes may adjust their nest defense behavior, but not egg rejection behavior, with seasonality.